Pelaksanaan Proses Peminatan Berdasarkan Implementasi Kurikulum 2013 Terhadap Tingkat Kepuasan Peserta Didik - Rulof Melmambessy (Jurnal Bimbingan dan Konseling Terapan, 2017)
Curriculum 2013 is a curriculum that prioritizes understanding, skills, and character education, students are required to understand the material, active in discussions and presentations and have a high discipline manners. In the 2013 curriculum, the division of departments through junior high school grades is done when students are still in class X. This study aims to determine the level of student satisfaction with the implementation of the division of majors conducted by the teachers at the time the students are still on Class X and based on SMP report cards. The department is one way to achieve the ideals and future of the students because the majors aim to develop the talents and abilities of the students. Instrument that researchers use is with the division of questionnaires, data collection techniques that the authors use are interviews, study libraries and documentation. Based on the research, it is found that the level of student satisfaction toward the implementation of departmental division based on the 2013 curriculum is very high or it can be said that the students who do not receive the results of the department division through the 2013 curriculum are very low. Therefore, the 2013 curriculum is very well used in the students next year or academic year 2017/2018.